2008
DOI: 10.1111/j.1464-410x.2008.07750.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic gene modification of skeletal muscle cells to compensate for ageing‐induced decline in bioengineered functional muscle tissue

Abstract: OBJECTIVE To explore the effects of ageing on the viability of bioengineered striated muscle tissue in vivo, and if this viability can be enhanced by concurrent neovascularization, as its utility for the treatment of stress urinary incontinence (SUI) might be reduced if muscle cells are derived from old patients. MATERIALS AND METHODS Myoblasts were obtained and expanded in culture from young (2 weeks), mature (3 months) and old (24 months) mice, and were engineered to express vascular endothelial growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…40 Although another recent report showed that myoblasts engineered to overexpress VEGF could overcome age-related declines in myogenic activity, the VEGF-engineered myoblasts led to an increase in the size and function of the bioengineered muscle as compared to nonengineered myoblasts. 41 Finally, we have observed a role for VEGF in graft success of cell transplantation to cardiac tissue. We showed that transplantation of MDSCs or VEGF-expressing MDSCs, but not sFlt-expressing MDSCs, prevents cardiac tissue remodeling and improves cardiac function after myocardial infarction in a mouse model.…”
Section: Discussionmentioning
confidence: 91%
“…40 Although another recent report showed that myoblasts engineered to overexpress VEGF could overcome age-related declines in myogenic activity, the VEGF-engineered myoblasts led to an increase in the size and function of the bioengineered muscle as compared to nonengineered myoblasts. 41 Finally, we have observed a role for VEGF in graft success of cell transplantation to cardiac tissue. We showed that transplantation of MDSCs or VEGF-expressing MDSCs, but not sFlt-expressing MDSCs, prevents cardiac tissue remodeling and improves cardiac function after myocardial infarction in a mouse model.…”
Section: Discussionmentioning
confidence: 91%
“…The proliferative capacity of satellite cells decreases with the age of the donor and also depends on the species and disease state of the donor. Furthermore, myosatellite cells are much more abundant in muscles of young animals than in muscles of older animals and thus, typically, neonatal individuals are selected for the isolation of these cells (Hawke and Garry 2001) that offer optimal regenerative potential and myofiber morphology (longer myofibers and greater myofiber density) in vitro (Delo et al 2008). For isolation, mincing of complete muscles is followed by enzymatic treatment and satellite cells are thereafter separated by differential centrifugation, preplating, precoll gradients, or a combination thereof.…”
Section: Culturing Of In Vitro Meatmentioning
confidence: 99%
“…2B). The gradual decrease in size due to collagen remodeling and myofiber formation has previously been reported (25) (Supplemental Fig. 2A).…”
Section: Histologic Assessment and Gene And Protein Analysis Of Harvementioning
confidence: 84%
“…Transplantation of muscle precursor cells has been contemplated as a treatment option for genetic and acquired muscle disorders (25,30) and as a prospective way to reestablish damaged muscle function in patients with muscle degeneration (31). Various research groups have demonstrated the formation of muscle tissue after cellular inoculation (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation